2018
DOI: 10.1371/journal.pgen.1007741
|View full text |Cite
|
Sign up to set email alerts
|

Deleterious variation shapes the genomic landscape of introgression

Abstract: While it is appreciated that population size changes can impact patterns of deleterious variation in natural populations, less attention has been paid to how gene flow affects and is affected by the dynamics of deleterious variation. Here we use population genetic simulations to examine how gene flow impacts deleterious variation under a variety of demographic scenarios, mating systems, dominance coefficients, and recombination rates. Our results show that admixture between populations can temporarily reduce t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
179
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(205 citation statements)
references
References 88 publications
(134 reference statements)
17
179
0
Order By: Relevance
“…This may reflect a positive effect (i.e., associative over‐dominance) of the presence of domestic ancestry in these regions. This interpretation is congruent with the hypothesis of temporarily reduced genetic load, caused by the masking of deleterious mutations, and resulting in an increase of introgressed ancestry as observed in a simulation study (Kim et al, ). This is also consistent with the expected higher accumulation of deleterious mutations in small lacustrine brook charr populations as observed by Ferchaud et al () as well as with the higher allelic richness observed in the domestic strain compared to these small lacustrine populations (Martin et al, ).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This may reflect a positive effect (i.e., associative over‐dominance) of the presence of domestic ancestry in these regions. This interpretation is congruent with the hypothesis of temporarily reduced genetic load, caused by the masking of deleterious mutations, and resulting in an increase of introgressed ancestry as observed in a simulation study (Kim et al, ). This is also consistent with the expected higher accumulation of deleterious mutations in small lacustrine brook charr populations as observed by Ferchaud et al () as well as with the higher allelic richness observed in the domestic strain compared to these small lacustrine populations (Martin et al, ).…”
Section: Discussionsupporting
confidence: 88%
“…Second, given the generally small effective population size of these brook charr lacustrine populations (Gossieux, Bernatchez, Sirois, & Garant, ), random drift may also be responsible for variable ancestry locally along the genome (Martin & Jiggins, ) and is not expected to produce consistent patterns across lakes. Third, the most likely evolutionary mechanism that could explain the general negative correlation would be a dominant effect of associative overdominance (Kim et al, ). Indeed, favoured domestic ancestry within regions of low recombination rate is likely to reflect the action of associative‐overdominance, especially if the recipient population tends to accumulate recessive deleterious alleles preferentially in low‐recombining regions (Charlesworth & Willis, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This disproportionate accumulation of deleterious variants on the Y may explain low rates of gene flow on the Y if, for example, selection is more effective in one population than another. Recent work simulating gene flow patterns between humans and Neanderthals, as well as between species of Arabidopsis, found that the gene flow landscape could be best explained by the differential accumulation of deleterious variation between genomic regions (Kim et al 2018). Similarly, lowered efficacy of selection on the Y due to linked selection could be an important driver of reduced gene flow on the Y chromosomes of R. hastatulus.…”
Section: The Large Sex Chromosome Effectmentioning
confidence: 99%